Challenges for Indonesia Zero Hunger Agenda in the Context of COVID-19 Pandemic - Paramashanti, Bunga Astria (UI Scholars Hub, 2020)
The rapid spread of COVID-19 has not only threatened the lives of the infected people but also socially and economically affected a broader community. The pandemic has also challenged the second goal of the 17 Sustainable Development Goals (SDGs) to eliminate all the forms of hunger by 2030. The most disadvantaged people may have a greater risk of having malnutrition and poor health as they cannot access a diet that is safe, nutritious, affordable, and sustainable. At this moment, saving lives by focusing on the health-care system should not be the only priority; the emphasis should be made in other essential aspects, including agri-food sector, in order not to cause any additional burden of hunger, malnutrition, and overall health.